Critical analysis of the weaknesses of the integrated reporting enterprise - Bezverkhiy, Kostiantyn (Herald of Economics, 2019)
Introduction. The modern reporting practices of both foreign and Ukrainian enterprises increasingly include integrated reporting. Identifying its benefits makes it a popular source of information for making appropriate managerial decisions, although the shortcomings of integrated reporting are not yet sufficiently explored. At the same time, the above topic of research is relevant and requires further scientific research in this direction.Purpose. The purpose of this study is to critically analyze the shortcomings of integrated reporting to build approaches to its implementation in domestic practice reporting based on foreign experience.Methods. Research methods such as analysis, synthesis, induction, deduction, abstraction, idealization, generalization and modeling were used for critical analysis of  the shortcomings of integrated reporting and the development of a matrix for the ratio of deficiencies in integrated reporting and the process of its formation.Results.  The  distribution  of  the  authors’  suggestions  concerning  the  allocation  of deficiencies of integrated reporting of the enterprise is presented. In the process ofscientific research, the analysis of the shortcomings of integrated reporting compared with traditional accounting reporting. The selected shortcomings of integrated reporting indicate that for the development and implementation of an efficient integrated reporting system of an individual enterprise it is necessary to take them into account. The author developed and proposed the matrix of the ratio of deficiencies of integrated reporting and the process of its formation, which allowed to outline the urgent issues regarding the formation of integrated reporting of an enterprise without the solution of which its further development in the practice of reporting delays, and their solution will accelerate the implementation of integrated reporting of enterprises both in Ukraine and abroad . The author highlights the disadvantages of integrated reporting, which until the time did not stand out in the writings of authors, namely: a) the lack of a single methodology for the preparation, compilation, submission, approval and disclosure of integrated reporting; b) involvement in the process of formation of integrated reporting not only the accounting service of the enterprise; c) a labor-intensive process of compiling integrated reporting; d) the absence of specialized software for the preparation, compilation and submission of integrated reporting. The scope of application of the results of research is recommended to all economic entities during the formation of the integrated reporting system of the enterprise.Discussion. In further scientific studies, it is proposed to focus on the development of an integrated reporting system for enterprises. In our opinion, this will enable the formation of a coherent, unified system of indicators of integrated reporting that will enable the comparability of integrated reports of different enterprises among themselves. This will be useful for both Ukrainian and foreign companies that make integrated reporting.